Mycorestoration of crude oil polluted soil using Pleurotus tuberregium - Beckley IKHAJIAGBE; Kingsley Erhons ENERIJIOFI; Paul O. UMENDU (Studia Universitatis Babeș-Bolyai. Biologia)
Crude oil contamination is known to cause unwholesome damage to man, his environment comprising of soil, air and water bodies as well as other forms of life. This study determined the effect of crude oil polluted soils on the composition of different microorganisms and plants and the growth of Pleurotus tuberregium. Oil polluted soils in bowls were amended with sawdust from Brachystegia nigerica as substrate. Fruiting bodies and the diameter of the mushroom cap were found to increase with increasing weeks of exposure to oil as against the control which had no fruiting bodies throughout the experiment. Pepperomia pellucida was found to be the predominant weed (n = 20), followed by Asystasia gangetica (n = 11). The bacterial and fungal counts were higher at the oil polluted soil attached to sclerotia than the control. The growth of Pleurotus tuberregium in the polluted soil samples showed its ability to degrade and utilize hydrocarbon as the source of carbon and energy, thereby remediating the contaminated soil environment. This work has shown that the fungus has bioremediation and pollution control capacity.